September Society - Finch, Charles (Thorndike, Me. : Center Point Pub., 2010)
In 1866, amateur detective Charles Lenox returns to his alma mater, Oxford, to search for a missing student which leads him to a much older, uglier mystery.
100102
Keywords: Lincoln College (University of Oxford); Private investigators -- England; Lenox, Charles (Fictitious character); Missing persons -- Investigation; College students -- England; Large type books; Historical fiction; Large type books; Mystery; Mystery fiction